Financial statement fraud casebook baking the ledgers and cooking the books - Wells, Joseph T. (Hoboken, New Jersey Wiley, 2011)
"A comprehensive look at financial statement fraud from the experts who actually investigated them. This collection of revealing case studies sheds clear insights into the dark corners of financial statement fraud. Includes cases submitted by fraud examiners across industries and throughout the world. Fascinating cases hand-picked and edited by Joseph T. Wells, the founder and Chairman of the world's leading anti-fraud organization ? the Association of Certified Fraud Examiners (ACFE) ? and author of Corporate Fraud Handbook. Outlines how each fraud was engineered, how it was investigated and how the perpetrators were brought to justice. Providing an insider's look at fraud, Financial Statement Fraud Casebook illuminates the combination of timing, teamwork and vision necessary to understand financial statement fraud and prevent it from happening in the first place"-- Provided by publisher.
Keywords: Misleading financial statements; Fraud